Career Counseling at the Universities: The Bangladesh Scenario - A. K. Ziauddin Ahmed; Laboni Ferdous; Abdullah Mohammad Sharif (European Scientific Journal, ESJ, 2017)
In the backdrop of growing diversity of educational programs and jobs this paper looks into the needs and realities of career counseling at the university level with particular reference to the public and private universities of Bangladesh. A sample of 72 universities was taken by random selection for the study. Qualitative data for six aspects of career counseling viz., existence of career counseling center, presence of professional career counselor, arrangement of career fair or job fair, internship placement services, job placement services, and existence of alumni association were then collected from the websites of these universities and/or over phone as was necessary. Collected data were analyzed using the statistical tools of tabulation, proportions, and chart. It was found that half of the universities of Bangladesh – both public and private – virtually do not have career counseling programs. The universities of Bangladesh need to recognize the importance of career counseling and employ attention and efforts in pertinent activities for their own interest.